Controlled breeding with norgestomet ear implant for induction of post partum oestrus in Deoni cows - MARKENDEYA, N M; BHARKAD, G P (The Indian Journal of Animal Reproduction, 2023)
Deoni com were treated for induction or oestrus with norgcslomct cur implants. All ( J 00%) o.nirnals responded to theueatm.cnl. The induced oestrus WM found to be ovulolDry In 90.00 per cent animals and 70.00 per cent cow, conceived with l 85services per conception.
Keywords: Deoni; oestrus; Norgestomct implnnt